Plaque Characteristics in Young Adults With Symptomatic Intracranial Atherosclerotic Stenosis: A Preliminary Study - Li, Ling; Tang, Min; Yan, Xuejiao; Gao, Jie; Ma, Niane; Shi, Xiaorui; Niu, Yaxin; Wen, Yu; Ai, Kai; Lei, Xiaoyan; Zhang, Xiaoling (Frontiers in Neurology, 2022)
Purpose: To determine how intracranial vascular wall and atherosclerosis plaque characteristics differ between young and old adults with sICAS. Methods: Eighty-four consecutive patients with sICAS who underwent high-resolution magnetic resonance imaging (HRMRI) from December 2017 to July 2020 were retrospectively collected. These participants were divided into young adult group (18-50 years, n = 28) and old adult group (>50 years, n = 56). Reviewers were blinded to any clinical information and HRMRI scans were analyzed for qualitative and quantitative indicators of vascular walls and plaque at the maximal lumen narrowing site using the independent-sample t test, Mann–Whitney U test, chi-square test or Fisher exact test, and logistic regression analysis. Results: Young patients with sICAS had significantly smaller maximum wall thickness (1.45 ± 0.38 mm2 vs.1.75 ± 0.51 mm2, P = 0.003), higher prevalence of positive remodeling (53.57% vs. 21.43%, P = 0.003), and lower prevalence of diabetes mellitus (14.29% vs. 35.71%, P = 0.04) than old patients. Plaque burden and other plaque features were comparable between young and old patients. Conclusion: Young patients with sICAS have smaller maximum wall thickness and greater ability to reconstruct, and are more likely to show positive remodeling, which may lead to some atherosclerotic lesions being missed. Young patients with evidence of vessel narrowing should be carefully examined for presence of high-risk atherosclerotic plaque.